The induction of aryl hydrocarbon receptor (AHR) in immune organs of developing chicks by polycyclic aromatic hydrocarbons - Nisha, A. R.; Hazilawati, H.; Mohd Azmi, M. L.; Noordin, M. M. (Taylor and Francis, 2018)
Polycyclic aromatic hydrocarbons are pollutants which are persistent in nature. The aryl hydrocarbon receptor is a ligand-activated cytosolic transcription factor activated by xenobiotics. The objective was to isolate and identify AHR mRNA transcript in immune organs of developing chicks and to interpret the correlation between AHR induction and dose of PAHs. Specific pathogen free embryonated eggs on day nine were inoculated with solutions of pyrene, phenanthrene, and fluoranthene dissolved in tricaprylin (vehicle) through the allantoic route at three dose levels: 0.2 mg/kg, 2 mg/kg, and 20 mg/kg. A 650 base pair product was observed by RNA extraction and reverse transcription PCR from thymus, bursa of Fabricius and spleen on 21st day. When AHR concentration was analyzed by ELISA in these organs, pyrene showed maximum potency in inducing AHR in thymus. Fluoranthene made highest concentration of AHR in bursa of Fabricius. None of these chemicals caused an increase in AHR concentration in spleen.